2013
DOI: 10.1111/sms.12025
|View full text |Cite
|
Sign up to set email alerts
|

Foot posture is associated with morphometry of the peroneus longus muscle, tibialis anterior tendon, and Achilles tendon

Abstract: The aim of this study was to investigate the association between foot type and the morphometry of selected muscles and tendons of the lower limb. Sixty-one healthy participants (31 male, 30 female; aged 27.1 ± 8.8 years) underwent gray-scale musculoskeletal ultrasound examination to determine the anterior-posterior (AP) thickness of tibialis anterior, tibialis posterior, and peroneus longus muscles and tendons as well as the Achilles tendon. Foot type was classified based on arch height and footprint measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
5
39
1
1
Order By: Relevance
“…Few studies done on the foot type and the TC morphometry opine that there exists an association between the two. Murley et al have found a positive correlation of TC morphometry with foot type 21 . According to Koivunen-Niemela & Parkkola, the flat arched foot type is often associated with a thinner TC tendon 9 .…”
Section: Study Done By Study Population Thickness Of Tcmentioning
confidence: 99%
“…Few studies done on the foot type and the TC morphometry opine that there exists an association between the two. Murley et al have found a positive correlation of TC morphometry with foot type 21 . According to Koivunen-Niemela & Parkkola, the flat arched foot type is often associated with a thinner TC tendon 9 .…”
Section: Study Done By Study Population Thickness Of Tcmentioning
confidence: 99%
“…This is supported by laboratory-based research using uninjured participants, which suggests that variations in foot posture (flat-and normal-arched feet) are associated with systematic differences in lower limb kinematics [6][7][8], kinetics [4,9,10], muscle function [11][12][13][14][15][16] and tendon morphometry [17].…”
Section: Introductionmentioning
confidence: 72%
“…Many researchers have used footprints as inclusion criteria for investigations. [16][17][18][19][20] However, the evaluation of foot structure, using footprints alone, is dubious, unless the relationship between footprints and foot posture is known. Footprints can influence clinicians and researchers to identify 'flat feet' from foot prints as a functionally 'pronated' foot (or 'cavus feet' from footprints as 'supinated' feet).…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Clinicians may use footprints for initial diagnosis or outcome indicators or for the use of foot orthoses. Many researchers have used footprints as inclusion criteria for investigations . However, the evaluation of foot structure, using footprints alone, is dubious, unless the relationship between footprints and foot posture is known.…”
mentioning
confidence: 99%